PROSES KOMUNIKASI PENGAMBILAN KEPUTUSAN ORANG TUA DALAM PERNIKAHAN DINI PADA ANAK DI BANJARNEGARA - Zidni Auliya Hanifa; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
This research is motivated by the authors' interest in the phenomenon of early marriage that occurs in Banjarnegara. The district is in the top 5 regions with the highest early marriage in Central Java in 2018. Marriage conducted by children is inseparable from the consent of parents because children cannot be said to be stable in decision making. The author conducted interviews with four informants from mothers and four informants from fathers who were having early marriages, with four different villages in Wanayasa. The analysis used phenomenology to see individual experiences in decision making, using interpretive paradigms. This study aims to look at how the communication process of parents' decision making in early marriage to children in Banjarnegara.Based on the results of the study, the authors see that the communication process of parents' decision making in early marriage to children is based on fear in the event of unwanted things such as adultery or pregnancy outside of marriage. The type of family communication among all informants is included in laissez faire because the communication patterns of parents and children are rare to create an incomplete communication relationship. Early marriage has also become a culture in the region and the community seems to perpetuate the phenomenon. An announcement of early marriage was formed that people were more willing to go through the process of dispensation of age in the Religious Courts to get married soon, rather than waiting to be old enough. Socialization from the Government or Social Institutions has also never been felt based on the statements of all informants, this has worsened the social conditions in the community because no one has rectified the phenomenon of seeing the risk of early marriage to the physical and psychological well-being of children, especially for women who will become pregnant.